Subthreshold ϕ meson production in nucleus-nucleus collisions - Piasecki K. (EPJ Web of Conferences, 2014)
Part of emission of the negatively charged kaons from the nucleus-nucleus collisions appears to originate from decays of ϕ(1020) mesons into the K+K− channel. We report on the measurement of the emission yield of ϕ mesons in the collisions of Ni+Ni at the beam kinetic energy of 1.91A GeV. The experiment was done with the FOPI spectrometer at the SIS 18 accelerator at GSI, Darmstadt. The total yield of ϕ was found to be (4.5 ± 0.7−1.2+1.8) · 10−4 per triggered event. Ratio of ϕ/K− emission yields was estimated at 0.42±0.13−0.11+0.17, meaning that about 20% of negatively charged kaons emitted from the collision originate from decays of ϕ mesons. The results are in agreement with similar HADES results done for the collisions of Ar+KCl.